Yue-bi-tang attenuates adriamycin-induced nephropathy edema through decreasing renal microvascular permeability via inhibition of the Cav-1/ eNOS pathway - Li, Tingting; Cheng, Su; Xu, Lin; Lin, Pinglan; Shao, Minghai (Frontiers in Pharmacology, 2023)
Edema is one of the most typical symptoms of nephrotic syndrome. Increased vascular permeability makes a significant contribution to the progression of edema. Yue-bi-tang (YBT) is a traditional formula with excellent clinical efficacy in the treatment of edema. This study investigated the effect of YBT on renal microvascular hyperpermeability-induced edema in nephrotic syndrome and its mechanism. In our study, the content of target chemical components of YBT was identified using UHPLC-Q-Orbitrap HRMS analysis. A nephrotic syndrome model was replicated based on male Sprague-Dawley rats with Adriamycin (6.5 mg/kg) by tail vein injection. The rats were randomly divided into control, model, prednisone, and YBT (22.2 g/kg, 11.1 g/kg, and 6.6 g/kg) groups. After 14 d of treatment, the severity of renal microvascular permeability, edema, the degree of renal injury, and changes in the Cav-1/eNOS pathway were assessed. We found that YBT could regulate renal microvascular permeability, alleviate edema, and reduce renal function impairment. In the model group, the protein expression of Cav-1 was upregulated, whereas VE-cadherin was downregulated, accompanied by the suppression of p-eNOS expression and activation of the PI3K pathway. Meanwhile, an increased NO level in both serum and kidney tissues was observed, and the above situations were improved with YBT intervention. It thus indicates YBT exerts therapeutic effects on the edema of nephrotic syndrome, as it improves the hyperpermeability of renal microvasculature, and that YBT is engaged in the regulation of Cav-1/eNOS pathway-mediated endothelial function.